Blocking DNA Damage Repair May Be Involved in Stattic (STAT3 Inhibitor)-Induced FLT3-ITD AML Cell Apoptosis - Luo, Yuxuan; Lu, Ying; Long, Bing; Lin, Yansi; Yang, Yanling; Xu, Yichuang; Zhang, Xiangzhong; Zhang, Jingwen (Frontiers in Cell and Developmental Biology, 2021)
The FMS-like tyrosine kinase 3 (FLT3)- internal tandem duplication (ITD) mutation can be found in approximately 25% of all acute myeloid leukemia (AML) cases and is associated with a poor prognosis. The main treatment for FLT3-ITD-positive AML patients includes genotoxic therapy and FLT3 inhibitors, which are rarely curative. Inhibiting STAT3 activity can improve the sensitivity of solid tumor cells to radiotherapy and chemotherapy. This study aimed to explore whether Stattic (a STAT3 inhibitor) affects FLT3-ITD AML cells and the underlying mechanism. Stattic can inhibit the proliferation, promote apoptosis, arrest cell cycle at G0/G1, and suppress DNA damage repair in MV4-11cells. During the process, through mRNA sequencing, we found that DNA damage repair-related mRNA are also altered during the process. In summary, the mechanism by which Stattic induces apoptosis in MV4-11cells may involve blocking DNA damage repair machineries